Penerapan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray untuk Meningkatkan Hasil Belajar Matematika XI IPA 3 SMAN 10 Medan - Siti Rahmah; Haryati Ahda Nasution; Cut Latifah Zahari; Ummi Aulia; Yofita Ningtias (Departement of Mathematics Education, 2024)
Class XI IPA 3 students at SMA Negeri 10 Medan will be using the TSTS cooperative learning paradigm to enhance their mathematical learning results. A total of thirty-two students participated in the research, which used Classroom Action Research (CAR). Conducted in two cycles, each cycle includes two sessions using the TSTS model and one session for evaluation. Data were collected through observations of teacher and student activities, as well as learning outcome tests. From the first to the second cycle, the findings demonstrate that both the teacher's and the students' actions significantly improve. During iteration two, teacher activity reached the